Системний принцип побудови автоматизованих навчальних систем - Стенін, О. А.; Польшакова, О. М.; Стенін, С. О.; Stenin, Alexander; Polshakova, Olga; Stenin, Sergey (КНТУ, 2016)
Запропонований системний принцип побудови автоматизованих навчальних систем (АНС), який передбачає реалізацію взаємопов'язаних етапів побудови АНС з єдиних системних позицій за допомогою різних математичних методів. An effective means to improve the training of operators are automated trainingsystems (ATS).In recent years, ATS in addition to traditional areas, such as aviation, aerospace, marine fleet are finding increasingly wide application in industry, energy and other sectors of the economy.Improvement of operator perfomance is the subject of a number of sciences and, in particular, the theory of ergatic systems. In this article the system principle of construction of ATS is proposed. This principle provides the implementation of interrelated stages of constructing ATS from single system point of view using variety of mathematical methods. It is an effective practical tools for constructing ATS for a wide class of ergatic objects with elements of decision making. In addition, this ATS significantly expands didactic opportunities for training operators of ergatic systems. The teacher (or instructor) in this ATS is an experienced specialist or his reference model.
System principle of the automated training systems
Keywords: автоматизована навчальна система; системний принцип; automated training system; system principle